The implementation of EU Optional Quality Term “Mountain Products” in Italy: Challenges and opportunities for the food sector in rural mountain areas - Bispini, Sara; Ievoli, Riccardo; Conti, Mauro; Belliggiano, Angelo (Economia agro-alimentare/Food Economy - Open Access, 2025)
The Optional Quality Term (OQT) “Mountain Product” aims to promote mountain food products. This term can be beneficial for the economy of mountain regions, as it allows them to distinguish their products and can protect consumers from fraud, counterfeiting or agro-piracy. This study has two main objectives: to assess how farms that have adopted the label perceive their limitations and to analyse the reasons for these limitations and provide policy recommendations to strengthen the use of OQT. The study involves a survey of agri-food companies that have adopted the label, with data collected through a questionnaire. Although existing research indicates that consumers generally prefer mountain products and perceive them as higher quality, producers report that consumer awareness of the OQT is still low. It appears essential to improve communication with both producers and consumers on the economic, social and environmental benefits of the ‘mountain product’ label. Producers need support to integrate the label into their business strategies, while consumers should be informed about the ethical and social responsibility linked to the OQT.